A comprehensive management of hypertension among patients with metabolic syndrome: an evidence-based update (Faculty of Medicine Universitas Indonesia, 2013)
Individuals with hypertension and metabolic syndrome are at increased risk of developing future morbidities. Therefore, an evidence-based comprehensive approach is required. It is recommended to start with lifestyle modification as the first step, then followed by antihypertensive drugs. Weight loss through decreased caloric intake and increased excercise have been proven to yield a better control over diabetes, blood pressure, and lipid profile. Inhibitor of renin-angiotensin is the recommended first-line drugs for this population, while β-blocker and diuretic should remain as the second line drugs due to increased risk of developing new onset diabetes with these drugs. A more rigorous blood pressure control is reasonable with a target of < 130/80 mmHg. A comprehensive management which include good control over blood pressure, weight, blood glucose, and lipid profile, may reduce future morbidities among hypertensive individuals with metabolic syndrome. (Med J Indones. 2013;22:189-94. doi: 10.13181/mji.v22i3.590)